Convection Boundary Layer Flows Over Needles and Cylinders in Viscous Fluids - Ahmad, Syakila (2009)
Convection is the heat transfer process which is frequently encountered in environmental and engineering applications. In this study, the problems of steady laminar convection boundary layer flows over needles and cylinders immersed in an incompressible and viscous fluid are theoretically considered. The dimensional partial differential equations governing the boundary layer flows are first transformed into nondimensional equations. These equations are then transformed using non-similar transformation. Then, these transformed nonlinear systems of equations are solved using an implicit finite difference scheme known as the Keller-box method, which has been found to be very suitable in dealing with nonlinear and parabolic equations. The complete numerical method used in this study is programmed in Fortran. Numerical computations are carried out for various values of the dimensionless parameters of the problems, which include the Prandtl number Pr, the ratio of the major and minor axes of the cylinder bc=ac, the mixed convection parameter , the modified mixed convection parameter ^, the transverse curvature parameter , the parameter a representing the needle size and the viscosity/temperature parameter r. Numerical results presented in this study are the skin friction coefficient, the heat transfer coefficient, the local Nusselt number, the cylinder temperature as well as the velocity and temperature profiles. The obtained results show that the flow and the thermal characteristics are significantly influenced by these parameters.